HABITATUL UMAN DIN MILENIUL I A. CHR. – PRIMA JUMĂTATE A MILENIULUI I P. CHR. ÎN BAZINUL RÂULUI COGÂLNIC - Sochircă, Vitalie; Matveev, Sergiu; Corobcean, Andrei; Vornic, Vlad (My University, 2020)
The article represents a synthesis of scientific knowledge on the habitat in the basin of the Cogalnic river and its archaeological component at the moment when we started an interdisciplinary project on research and scientific valorization of the archaeological heritage of the Iron Age in the basin of Cogalnic river from the Republic of Moldova. Related to the way of life of human communities of the Iron Age are presented historical, geographical, geological peculiarities; also: relief, climate, vegetation, animals and soil of the researched micro-region, followed by a repertory of archaeological sites corresponding chronologically and geographically to the researched topic, accompanied by a history of their study with the identification of the main stages and the most involved researchers.

Articolul prezintă rezultatele prospectării nivelului de cunoaștere privind habitatul bazinului râului Cogâlnic și siturile arheologice în momentul demarării unui proiect interdisciplinar privind cercetarea și valorificarea științifică a patrimoniului arheologic din epoca fierului din bazinul râului Cogâlnic de pe teritoriul Republicii Moldova. În legătură directă cu modul de viață a comunităților umane din această epocă sunt prezentate aspecte istorico-geografice, geologice, relieful, clima, vegetația, lumea animală și solul microregiunii cercetate, după care urmează un repertoriu al siturilor arheologice corespondente cronologic și geografic temei studiate, însoțit de un istoric al studierii lor cu identificarea principalelor etape și a cercetătorilor implicați.

статье представлен синтез научных знаний о среде обитания в бассейне реки Когыльник и ее нагрузке археологической составляющей в момент начала междисциплинарного проекта по исследованию и научному освоению археологического наследия железного века в бассейне р. Когыльник на территории Республики Молдова. В прямой связи с образом жизни человеческих сообществ этой эпохи представлены историко-географические и геологические аспекты, рельеф, климат, растительность, животный мир и почвы исследуемого микрорегиона. Далее следует свод археологических памятников, хронологически и географически соответствующих исследуемой теме, сопровождаемый историей их изучения с указанием основных этапов и наиболее вовлеченных исследователей.
The uman habitat from the 1st millennium BC - first half of the 1st millennium AD in the basin of the Cogalnic river
Среда обитания человека I-го тысячелетия до н.э. – первой половины I-го тысячелетия н.э. в бассейне реки Когыльник
Keywords: human habitat; Iron Age; great migration period; среда обитания человека; железный век; великое переселение; human habitat; epoca fierului; perioada marilor migrații; râul Cogâlnic